Hydrostatic Pressure Regulates the Volume, Aggregation and Chondrogenic Differentiation of Bone Marrow Derived Stromal Cells - Aprile, Paola; Kelly, Daniel J. (Frontiers in Bioengineering and Biotechnology, 2021)
The limited ability of articular cartilage to self-repair has motivated the development of tissue engineering strategies that aim to harness the regenerative potential of mesenchymal stem / marrow stromal cells (MSCs). Understanding how environmental factors regulate the phenotype of MSCs will be central to unlocking their regenerative potential. The biophysical environment is known to regulate the phenotype of stem cells, with factors such as substrate stiffness and externally applied mechanical loads known to regulate chondrogenesis of MSCs. In particular, hydrostatic pressure (HP) has been shown to play a key role in the development and maintenance of articular cartilage. Using a collagen-alginate interpenetrating network (IPN) hydrogel as a model system to tune matrix stiffness, this study sought to investigate how HP and substrate stiffness interact to regulate chondrogenesis of MSCs. If applied during early chondrogenesis in soft IPN hydrogels, HP was found to downregulate the expression of ACAN, COL2, CDH2 and COLX, but to increase the expression of the osteogenic factors RUNX2 and COL1. This correlated with a reduction in SMAD 2/3, HDAC4 nuclear localization and the expression of NCAD. It was also associated with a reduction in cell volume, an increase in the average distance between MSCs in the hydrogels and a decrease in their tendency to form aggregates. In contrast, the delayed application of HP to MSCs grown in soft hydrogels was associated with increased cellular volume and aggregation and the maintenance of a chondrogenic phenotype. Together these findings demonstrate how tailoring the stiffness and the timing of HP exposure can be leveraged to regulate chondrogenesis of MSCs and opens alternative avenues for developmentally inspired strategies for cartilage tissue regeneration.